2011
DOI: 10.1097/aog.0b013e31822e1264
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Fetal Echocardiography After an Unremarkable Anatomy Scan

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…The overall higher rate of diagnosis by the pediatric cardiologists might be explained by the fact that, in most cases, antenatal pediatric fetal echocardiogram was performed at about 22 weeks or later while the initial MFM study was performed at 16–21 weeks for the great majority of cases. One would expect that the optimal technical study terms in the early neonatal period would result in better diagnosis when performed by experienced and skilled pediatric cardiologist as has been previously reported [8, 9, 11, 12]. This is further supported by the two cases in which both the MFM physicians and the pediatric cardiologists failed to correctly identify major cardiac abnormalities in the same two fetuses.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The overall higher rate of diagnosis by the pediatric cardiologists might be explained by the fact that, in most cases, antenatal pediatric fetal echocardiogram was performed at about 22 weeks or later while the initial MFM study was performed at 16–21 weeks for the great majority of cases. One would expect that the optimal technical study terms in the early neonatal period would result in better diagnosis when performed by experienced and skilled pediatric cardiologist as has been previously reported [8, 9, 11, 12]. This is further supported by the two cases in which both the MFM physicians and the pediatric cardiologists failed to correctly identify major cardiac abnormalities in the same two fetuses.…”
Section: Discussionsupporting
confidence: 59%
“…Diagnosis agreement in these studies ranged 38% to 100%. Some of the authors concluded that fetal echocardiography by pediatric cardiologists adds little to the care of women with no suspected heart disease on a detailed anatomic survey by OBGYN/MFM physician [9, 10], while others concluded that improved accuracy in diagnosis can be achieved through a pediatric cardiologist with special skills in fetal echocardiography working collaboratively with obstetric sonographers and sonologists to optimize the details of diagnosis [8, 9, 11, 12]. Naturally, the latter studies had lower level of diagnostic accuracy and agreement in comparison to the former studies.…”
Section: Introductionmentioning
confidence: 99%
“…The fetal echocardiographic examinations were performed by an experienced fetal medicine consultant or by a fetal cardiologist. Recent reports have shown that fetal echocardiography may be of limited benefit after normal anatomy scan results have been obtained at an institution where a high volume of sonographic examinations are performed or where the examinations are read by maternal‐fetal medicine specialists …”
Section: Discussionmentioning
confidence: 99%
“…Prior to the universal recommendation of implementing views of the outflow tracts, some advocated for universal fetal echocardiography screening due it its high sensitivity for the detection of CHD . However, since the inclusion of the outflow tracts into the detailed ultrasound, some question the role of screening fetal echocardiogram in the presence of a normal cardiac exam on a detailed ultrasound . Although fetal echocardiography improves detection rates over routine anatomical screening, it is technically demanding and expensive .…”
Section: Introductionmentioning
confidence: 99%